Nano-encapsulated organic phase change material based on copolymer nanocomposites for thermal energy storage - Khadiran, Tumirah; Hussein, Mohd. Zobir; Zainal, Zulkarnain; Rusli, Rafeadah (Elsevier, 2014)
This study deals with fabrication, physico–chemical characterizations and thermal properties of n-octadecane nanocapsules as organic PCM (phase change materials) for TES (thermal energy storage). Nano-encapsulated organic PCM was fabricated by encapsulation of n-octadecane as a core with St (styrene) – MMA (methylmethacrylate) copolymer shell using miniemulsion in-situ polymerization method. The influence of St/MMA and n-octadecane/copolymer mass ratio on the encapsulation processes, physico–chemical and thermal properties of the resulting nanocapsules has been studied systematically. DSC (differential scanning calorimeter) analysis indicated that the n-octadecane in the nanocapsules form melts at 29.5 °C and crystallize at 24.6 °C. N-octadecane nanocapsules has an enthalpy of 107.9 and 104.9 Jg-1 for melting and crystallization, respectively. TGA (thermal gravimetric analysis) thermograms showed that the nano-encapsulated organic PCM degraded in two distinguishable steps and has a good chemical stability. The thermal cycling test of the nanocapsules was carried out for 360 heating/cooling cycles and indicates that the developed nanomaterial has good chemical stability and thermal reliability. Based on all the results obtained, it can be concluded that n-octadecane/St-MMA nanocapsules have potential for thermal energy storage for buildings and other applications.